Alkyl polyglycoside, a highly promising adjuvant in intranasal split influenza vaccines. Issue 6 (3rd June 2017) - Wu, Hui; Bao, Yuanyuan; Wang, Xiang; Zhou, Dongming; Wu, Wenzhe
ABSTRACT: Influenza viral infections are significant global public health concerns due to the morbidity and mortality associated with acute respiratory disease, secondary complications, and pandemic threats; thus, continuous efforts have been made to develop potent influenza vaccines. In this study, 3 different mucosal adjuvants—alkyl polyglycoside (APG), gellan gum, and chitosan (CS)—were evaluated for their efficacy in intranasal A/H1N1 or B split influenza vaccines administered to BALB/c mice. Protective immunity was monitored by serum analysis for IgG, hemagglutination inhibition (HI), and neutralizing antibody levels, as well as mucosal IgA levels in nasal and pulmonary lavage fluids. Survival, body weight, lung viral titer, and pulmonary immunopathology were also examined following lethal influenza challenge. Notably, all adjuvants amplified the IgG and IgA immune responses (not detected in immunization of influenza B) and increased survival rate compared with controls administered adjuvant-free intranasal vaccines. Alternatively, intramuscular immunization stimulated IgG production, but had no effect on IgA levels. Our collective analysis identified that APG was the most effective intranasal adjuvant, as all mice survived influenza challenge with limited body weight loss, viral titer, and pulmonary pathology, similar to those observed with intramuscular vaccination. This evidence supports that APG can elicit both systemic and mucosal immunity, and may be an effective adjuvant in intranasal split influenza A/H1N1 and B vaccines.